2015
DOI: 10.1136/bcr-2014-207109
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus due to extreme dilation of Virchow-Robin spaces

Abstract: SUMMARYVirchow-Robin spaces (VRS) are extensions of the subarachnoid space surrounding perforating blood vessels entering the brain parenchyma. VRS are fluid filled, but almost virtual and only visible on MRI of the brain when dilated. Such dilations are commonly asymptomatic. In rare cases, extreme dilations can be observed; the clinical repercussions of which remain unclear. We report the case of a patient presenting symptoms of normal pressure hydrocephalus due to extreme VRS mesencephalon dilations. BACKGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…2) reported in this study are consistent with earlier reports on the ultrastructure of human and rabbit syrinx cavities [14,15,32,33]. Interestingly, enlarged perivascular spaces were also reported in hydrocephalus [34][35][36] and a number of cerebrovascular and systemic pathologies including small vessel disease [37,38], moyamoya disease [39], ischemic and lacunar stroke [40], lupus erythematosus [41], and arteriosclerosis [42]. Despite frequent reports [34][35][36][37][38][39][40][41][42], the significance of enlarged perivascular spaces remains unclear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2) reported in this study are consistent with earlier reports on the ultrastructure of human and rabbit syrinx cavities [14,15,32,33]. Interestingly, enlarged perivascular spaces were also reported in hydrocephalus [34][35][36] and a number of cerebrovascular and systemic pathologies including small vessel disease [37,38], moyamoya disease [39], ischemic and lacunar stroke [40], lupus erythematosus [41], and arteriosclerosis [42]. Despite frequent reports [34][35][36][37][38][39][40][41][42], the significance of enlarged perivascular spaces remains unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, enlarged perivascular spaces were also reported in hydrocephalus [34][35][36] and a number of cerebrovascular and systemic pathologies including small vessel disease [37,38], moyamoya disease [39], ischemic and lacunar stroke [40], lupus erythematosus [41], and arteriosclerosis [42]. Despite frequent reports [34][35][36][37][38][39][40][41][42], the significance of enlarged perivascular spaces remains unclear. There is a possibility that blood vessels with enlarged perivascular spaces are initially involved in the process of syrinx formation, however there was no explicit evidence of enlarged perivascular spaces directly feeding into the cavities in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] were excluded since no individual clinical or radiological features were described in their study to allow in-depth analysis. [ 1 4 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 ] Our pooled analysis showed that 49% (18/37) of TPVSs in this group had accompanying midbrain-localizing neurological signs. Apart from hemiparesis, patients were reported to have rubral tremors, oculomotor nerve palsy, Benedikt's syndrome, Parkinsonism, Parinaud's syndrome, and cerebellar ataxia.…”
Section: Discussionmentioning
confidence: 67%
“…Increase in size Rocha et al/2013 [23] 52/female Cognitive decline and unsteady gait [20] 43/female Drowsiness, vomiting, and diplopia 3 days Mesencephalondiencephalon junction III ETV NA Choh et al/2014 [24] NA/male Headache and unsteady gait 2 years Mesencephalondiencephalon junction III VP shunt NA Revel et al/2015 [25] 74/male Cognitive decline, unsteady gait and urinary incontinence [27] 50/male Unsteady gait, headache, and blurring of vision NA Mesencephalon III ETV and cyst fenestration Yes Donaldson et al/2017 [28] 31/male Pulsatile tinnitus and headache 1 month Mesencephalondiencephalon junction…”
Section: Etv and Cyst Fenestrationmentioning
confidence: 99%
“…Seven months after initial presentation, headache and visual disturbances increased and temporarily became worse as a result of slight head injuries [75]. One patient who was treated with a ventriculoatrial shunt presented with hyperdrainage symptoms and subdural hematoma one month later, which was evacuated without further complications [15]. In the majority of patients who underwent direct surgery of tumefactive VRs (mainly by cyst fenestration), the tumefactive VRs reduced and remained stable during follow-up.…”
Section: Literature Searchmentioning
confidence: 99%